Contextual effects on the free kick performance. A case study with a Portuguese professional soccer team - Corbellini, F.; Volossovitch, A.; Andrade, C.; Fernandes, O.; Ferreira, A. P. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Free kicks (FK) represent one of the most relevant events for the offensive process efficacy in high performance soccer, providing between 15% and 20% of goals scored (Acar, 2009; Alcock, 2010). This study aimed to assess the effect of match status and quality of opposition on the way to perform and subsequent success of FK in matches of a professional soccer team. Methods The sample consisted of 89 FK, marked in the offensive field, in ten matches of the Portuguese Professional Soccer League and Portugal Cup 2009/2010 played by observed team. The observation system, developed for this study, included 7 categories and 37 performance indicators that were analyzed in function of two contextual variables . match status and quality of opposition. Descriptive statistics and Hierarchical log-linear models were used for analysis of relationship between performance and contextual variables. Results & Discussion The results showed that in score disadvantage: 1) the observed team made significantly more FK, especially in the last periods of match (60-75 min and 75-90 min) (p.0,001); 2) the number of fouls marked in favor of the team in the central areas of the field raised (p. 0,035); 3) the first contact with the ball after FK occurred mainly in the center areas, near to the penalty area (p.0,005). When the team was winning, the players made more successful final shot from the sides of penalty area (p.0,005). The quality of opposition didn't show any significant effect on the team performance in free kick. Conclusion It was concluded that match status had significant effect on the team's actions in FK situations. Being behind in score, the observed team showed more offensive play, using field's center areas; suffer more fouls and, as a consequence, made more successful final shots from FK. The absence of quality of opposition effect on the team's performance in FK situations might be explained by low ranking of the observed team.